2016
DOI: 10.1016/j.jadohealth.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Care Missed Opportunity: Preexposure Prophylaxis and Young Black Men Who Have Sex With Men

Abstract: HIV disproportionately impacts young Black men who have sex with men (YBMSM). Pre-exposure prophylaxis (PrEP) is an effective strategy that can avert new HIV infections in YBMSM. Barriers exist for YBMSM to access PrEP. We sought to determine factors associated with awareness of and willingness to take PrEP in a sample of YBMSM. Only 8% were currently on PrEP despite many (66%) reporting condomless anal sex, a recent provider visit (54%), disclosing their sexual orientation to their regular medical provider (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
2
34
0
Order By: Relevance
“…The proportions of patients who expressed awareness of and willingness to take PrEP in our population were similar to those noted in other studies (Arrington-Sanders et al, 2016;Eaton, Matthews et al, 2017;Philbin et al, 2016). Being asked by a provider about sexual-related behaviors and one's sexual orientation and having been hurt by a partner increased the odds of willingness to take PrEP, as did having provider-initiated discussions about HIV/STI risk reduction and condom use.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The proportions of patients who expressed awareness of and willingness to take PrEP in our population were similar to those noted in other studies (Arrington-Sanders et al, 2016;Eaton, Matthews et al, 2017;Philbin et al, 2016). Being asked by a provider about sexual-related behaviors and one's sexual orientation and having been hurt by a partner increased the odds of willingness to take PrEP, as did having provider-initiated discussions about HIV/STI risk reduction and condom use.…”
Section: Discussionsupporting
confidence: 85%
“…Coming to see a provider to get condoms or for STI testing were both associated with willingness to take PrEP, whereas coming to the provider for a routine or non-STD related sick visit were not associated with either awareness of or willingness to take PrEP. These findings extend prior studies that have found that individuals reporting higher-risk sexual behaviors are more willing to take PrEP, and identify visit type opportunities that providers should not miss to discuss and offer prep, as indicated (Arrington-Sanders et al, 2016;Jones et al, 2014;Perez-Figueroa, Kapadia, Barton, Eddy, & Halkitis, 2015). Further study is needed in how to promote providers to take advantage of such opportunities to augment PrEP uptake among those patients who are ready.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In most of the studies, they were young and lived in or migrated into big cities. Several of studies conducted in the United States focused on ethnic minorities including African American ( Arrington-Sanders et al, 2016 ) and Hispanic/Latino populations ( Joseph et al, 2014 ; Oster et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, the target of disclosure was generally referred as health-care providers. Some studies used the term “doctors” and “physicians” ( Koch et al, 2016 ; Petroll & Mosack, 2011 ), some used the term “(regular) doctor, nurse, or healthcare providers” ( Ramirez-Valles et al, 2014 ; Wall et al, 2010 ), or “health-care professional” ( Ng et al, 2014 ; Tang et al, 2017 ; Wilkerson et al, 2010 ) or “medical provider” ( Arrington-Sanders et al, 2016 ). Some studies explicitly focused on general practitioners (GPs) ( Fitzpatrick et al, 1994 ; Ludlam et al, 2015 ; Metcalfe et al, 2015 ) and primary health-care provider ( Marcus et al, 2015 ; Petroll & Mitchell, 2015 ).…”
Section: Resultsmentioning
confidence: 99%